The global research of artificial intelligence in lung cancer: a 20-year bibliometric analysis - Zhong, Ruikang; Gao, Tangke; Li, Jinghua; Li, Zexing; Tian, Xue; Zhang, Chi; Lin, Ximing; Wang, Yuehui; Gao, Lei; Hu, Kaiwen (Frontiers in Oncology, 2024)
Background：Lung cancer (LC) is the second-highest incidence and the first-highest mortality cancer worldwide.Early screening and precise treatment of LC have been the research hotspots in this field. Artificial intelligence (AI) technology has advantages in many aspects of LC and widely used such as LC early diagnosis, LC differential classification, treatment and prognosis prediction.Objective：This study aims to analyze and visualize the research history, current status, current hotspots, and development trends of artificial intelligence in the field of lung cancer using bibliometric methods, and predict future research directions and cutting-edge hotspots.Results：A total of 2931 articles published between 2003 and 2023 were included,contributed by 15,848 authors from 92 countries/regions.Among them, China (40%) with 1173 papers ,USA (24.80%) with 727 papers and the India(10.2%) with 299 papers have made outstanding